Stellarator-tokamak energy confinement comparison based on ASDEX Upgrade and Wendelstein 7-X hydrogen plasmas. (23rd November 2020) - Stroth, U.; Fuchert, G.; Beurskens, M.N.A.; Birkenmeier, G.; Schneider, P.A.; Scott, E.R.; Brunner, K.J.; Günzkofer, F.; Hacker, P.; Kardaun, O.; Knauer, J.P.; Rahbarnia, K.; et al.
Abstract: A confinement database with mainly electron-heated hydrogen plasmas from ASDEX Upgrade and Wendelstein 7-X was assembled. Stellarator confinement scaling expressions describe both standard discharges in the stellarator and L-mode plasmas in the tokamak similarly well and indicate a similar quality of energy confinement in both devices. While the energy confinement time in ASDEX Upgrade benefits from the smaller aspect ratio of the device, the transport coefficients in Wendelstein 7-X appear to be smaller possibly due to reduced average magnetic field curvature. A physics based confinement scaling is derived from a model that successfully describes transport in tokamaks. The dimensionally correct scaling has very similar parameter dependencies as the stellarator scalings and reproduces also the trends in the data from ITER L- and H-mode databases reasonably well. On the basis of this scaling, which represents the confinement times of the present data base, average tokamak L-mode and H-mode confinement is 7% lower and 76% higher, respectively.